Models and scalings for the disruption forces in tokamaks. (5th January 2022) - Pustovitov, V.D.
Abstract: The study is devoted to theoretical analysis of some models for calculating the disruption forces in tokamaks and scalings for these forces which can be proposed for ITER. It is motivated by the necessity of reliable predictions for ITER. The task includes the evaluation of the existing models, resolution of the conflicts between them, elimination of contradictions by proper improvements, elaboration of recommendations for dedicated studies. Better qualities of the modelling and higher accuracy are the ultimate theoretical goals. In recent years, there was a steady progress in developing a physics basis for calculating the forces, which gave rise to new trends and ideas. It was discovered, in particular, that the wall resistivity, penetration of the magnetic perturbation through the wall, the poloidal current induced in the wall, the kink-mode coupling, plasma position in the vacuum vessel must be the elements essentially affecting the disruption forces. These and related predictions along with earlier less sophisticated concepts and results are analysed here.